PENGARUH BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN KINERJA LINGKUNGAN SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia periode 2017-2022) - Sari, Melinda (JURNAL RISET AKUNTANSI TIRTAYASA, 2023)
This study aims to investigate the effect of Environmental Costs on Financial Performance with Environmental Performance as the intervening variable. Financial performance is proxied by Return on Equity and environmental performance is proxied by PROPER rating. The research population includes mining companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sampling method applied in this research was purposive sampling and selected 19 companies with a total sample of 69 research data. The hypothesis in this study was tested by applying path analysis and Sobel test. The research results show that environmental costs have an effect on financial performance, whereas environmental costs have no effect on environmental performance. Environmental performance has no effect on financial performance and environmental performance does not act as a mediator between environmental costs and financial performance.